2020
DOI: 10.1080/13696998.2020.1722138
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness and impact on quality of life of abobotulinumtoxinA and onabotulinumtoxinA in the treatment of children with lower limb spasticity in Canada

Abstract: Background: Injectable botulinum neurotoxins are a mainstay of treatment for pediatric spasticity. AbobotulinumtoxinA and onabotulinumtoxinA are both injectable toxin therapies used to treat pediatric lower limb (PLL) spasticity in Canada. The objective of this study was to assess the cost-effectiveness of abobotulinumtoxinA vs. onabotulinumtoxinA in the treatment of PLL spasticity in Canada. Methods: A probabilistic Markov cohort model with a 2-year time horizon was developed, with health states defined by re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The presented clinical and economic findings are in line with earlier analyses. One published NMA 23 and one published cost-effectiveness analysis 24 compared the efficacy and costeffectiveness of BoNT-A therapies for the treatment of children with spasticity in the lower limbs, though this study is the first to evaluate children with spasticity in the upper limbs and from a UK NHS perspective. The previous NMA found that aboBoNT-A (15U/kg and 10U/kg in each leg) was more efficacious than onaBoNT-A (4U/kg per leg, 4U/kg per leg+casting, 4U/kg, and 8U/kg) in terms of MAS at 12-weeks in children with lower limb spasticity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The presented clinical and economic findings are in line with earlier analyses. One published NMA 23 and one published cost-effectiveness analysis 24 compared the efficacy and costeffectiveness of BoNT-A therapies for the treatment of children with spasticity in the lower limbs, though this study is the first to evaluate children with spasticity in the upper limbs and from a UK NHS perspective. The previous NMA found that aboBoNT-A (15U/kg and 10U/kg in each leg) was more efficacious than onaBoNT-A (4U/kg per leg, 4U/kg per leg+casting, 4U/kg, and 8U/kg) in terms of MAS at 12-weeks in children with lower limb spasticity.…”
Section: Discussionmentioning
confidence: 99%
“…21 The previous cost-effectiveness analysis found that aboBoNT-A was dominant compared with onaBoNT-A for the treatment of children with spasticity in the lower limbs in Canada. 24 A retrospective chart review of adults and children in the USA found that substituting onaBoNT-A with aboBoNT-A for the treatment of limb spasticity and cervical dystonia would result in a cost savings of $259, 131 (2017/18 US dollars) across a fivehospital healthcare system. 70 This is also consistent with findings by independent authors based on claims analyses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations